Effect of adjuvant radiotherapy on survival in resected pancreatic cancer: A propensity score surveillance, epidemiology, and end results database analysis. Issue 8 (21st August 2014) - Sugawara, Akitomo; Kunieda, Etsuo
<x xml:space="preserve">Abstract</x> Background and Objectives The role of adjuvant radiotherapy for resected pancreatic cancer remains controversial. The aim is to demonstrate a survival benefit of adjuvant radiotherapy for resected pancreatic cancer. Methods The Surveillance, Epidemiology and End Results database was used to identify patients who were diagnosed with adenocarcinoma of the pancreas from 2004 to 2009, underwent cancer‐directed surgery, and received either no radiotherapy or postoperative radiotherapy. Kaplan–Meier and multivariable Cox proportional hazards analyses using a propensity score matching were conducted to determine the effect of adjuvant radiotherapy on overall and disease‐specific survival. Results A total of 2, 532 patients were included. The median overall and disease‐specific survival were significantly longer in the adjuvant radiotherapy group than in no radiotherapy group (overall survival, 20 months vs. 16 months, respectively; disease‐specific survival, 22 months vs. 18 months, respectively; both P < 0.0001). In multivariable Cox proportional analyses, adjuvant radiotherapy was associated with a significant overall and disease‐specific survival benefit (both P < 0.001). Conclusions There is a survival benefit of adjuvant radiotherapy in patients with resected pancreatic cancer. We concluded that adjuvant radiotherapy might be included in the standard treatment for resected pancreatic cancer. J. Surg. Oncol. 2014; 110:960–966. © 2014 Wiley Periodicals, Inc.